Analysis of a pilot-scale constructed wetland treatment system for flue gas desulfurization wastewater - Talley, Mary Katherine (Kansas State University, 2012)
Coal-fired generation accounts for 45% of the United States electricity and generates harmful emissions, such as sulfur dioxide. With the implementation of Flue Gas Desulfurization (FGD) systems, sulfur dioxide is removed as an air pollutant and becomes a water pollutant. Basic physical/chemical wastewater treatment can be used to treat FGD wastewater, but increased regulations of effluent water quality have created a need for better, more economical wastewater treatment systems, such as constructed wetlands. At Jeffrey Energy Center, north of St. Mary’s, KS, a pilot-scale constructed wetland treatment system (CWTS) was implemented to treat FGD wastewater before releasing the effluent into the Kansas River. The objectives of this study were to 1.) determine if a portable water quality meter could be used to assess water quality and track pollutant concentrations, 2.) develop a water balance of the CTWS, 3.) generate a water use coefficient for the CWTS, and 4.) create a mass balance on the pollutants of concern. Water quality measurements were taken with a HORIBA U-50 Series Multi Water Quality Checker and compared to analytical water tests provided by Continental Analytic Services, Inc. (CAS) (Salina, KS). The water balance was created by comparing inflows and outflows of data determined through flow meters and a Vantage Pro2™ weather station. Information from the on-site weather station was also used to compute the system water use coefficient. Water sampling was conducted from date to date at 10 locations within the CWTS. In general, there was little to no relationship between the HORIBA water quality measurements and the analytical water tests. Therefore, it was recommended that JEC continue to send water samples on a regular basis to an analytical testing laboratory to assess the CWTS function and track pollutants of concern. Because the water balance was conducted during system initiation, there was a great deal of fluctuation due to problems with the pumping system, issues with the upstream FGD treatment system, extreme weather events, and immature vegetation. This fluctuation resulted in the system having a non-steady state operation, which weakened the ability to calculate a system water use coefficient. However, during periods of strong system function, the water use coefficient was similar to previous studies with maximum water use being approximately equal to the reference evapotranspiration. The results of the mass balance indicated high removals mercury, selenium, and fluoride, but low removals of boron, manganese, chloride, and sulfate were exported from the CWTS.
Keywords: Constructed wetlands; Flue gas desulfurization; Coal fired power plants; Wastewater; FGD; Engineering (0537); Engineering, Agricultural (0539); Environmental Engineering (0775)